Development of the “Yak Meureunoe Bahasa Aceh” Mobile Learning Application - Munthe, Sediken Tara; Mukramah, Mukramah; Santika, Cut; Masyitah, Masyitah (Indonesian Journal of Education Methods Development, 2025)
General Background: The preservation of regional languages in Indonesia faces serious challenges due to globalization and the declining interest of younger generations in using local languages. Specific Background: The Acehnese language, as a carrier of rich cultural and philosophical values, has experienced a reduction in daily use, necessitating innovative educational media that align with digital learning trends. Knowledge Gap: Current Acehnese language instruction still relies on conventional methods that lack interactivity and technological integration. Aims:This study aims to design and develop the “Yak Meureunoe Bahsa Aceh” mobile-based learning application using the 4D model (Define, Design, Develop, Disseminate) to enhance learning motivation and preserve the Acehnese language. Results: Validation results from linguists, media experts, and language teachers yielded an average feasibility score of 82.7% (highly feasible), while field trials showed a learning motivation increase with a mean score of 78.7%. Novelty: The application integrates linguistic accuracy, interactive design, and accessibility through mobile technology, making it the first comprehensive Acehnese language learning tool based on the 4D model. Implications: This innovation provides an effective medium for regional language revitalization, supports independent learning, and serves as a model for developing digital learning applications for other local languages Highlights: Promotes regional language preservation through digital learning. Uses the 4D model to ensure systematic application development. Increases student motivation and engagement in language learning. Keywords: Acehnese Language, Mobile Learning, 4D Model, Language Preservation, Educational Technology